Digital Tools for Structure in a Mainstream Class - Mirjam Harkestad Olsen (University of Aberdeen, School of Education, 2018)
The subject of the article is how digital structure and predictability affects the learning environment. This is key knowledge as regards both class management and learning. An intervention research design was employed. The intervention aimed to test digital aids in a mainstream class: a digital day planner board and a Time timer wristwatch with a countdown function. These aids are usually allocated to individual pupils. Two classes, with 16 and 17 students respectively, were included in the study. Three of them had neurobiological disorders such as ADHD, Tourette's syndrome and ODD. Before the project period, there was considerable unrest in the classes. The data set is based on focus group interviews, observations and conversations with pupils. We also gathered the teachers' change narratives. The material will be analysed and assessed in relation to other studies on the impact of digital aids for this group of pupils. Teachers' feedback shows that the digital timetable board helps them to visualise the day's structure, and they note that pupils with special needs use the board to orientate themselves during the day. The countdown function has created greater calm during activities. Pupils report that they like knowing how long the activity will last - this provides a sense of calm.